PENGARUH WHISTLEBLOWING DAN PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN KORUPSI (Studi Empiris pada Inspektorat Provinsi Jawa Tengah) - Rachmatika Ane Riane; Siti Mutmainah (Diponegoro Journal of Accounting, 2025)
This study aims to test hypotheses and produce empirical findings related to the effect of whistleblowing and internal control on corruption prevention at the Inspectorate of Central Java Province. This study uses primary data using a questionnaire with purposive sampling technique. The number of samples was 50 samples. Hypothesis testing in this study uses multiple linear regression analysis with the help of the SPSS version23 program. The independent variables used are whistleblowing and internal control. The indicators used to measure whistleblowing use the guidelines of the National Committee on Governance Policy (2008), while internal control is measured by Committee of Sponsoring Organizations of the Treadway Commission. The dependent variable in the form of corruption prevention is measured using the proxy of the fraud diamond. The results showed that whistleblowing has a negative effect on corruption prevention, while internal control has an effect on corruption prevention.